STUDENTS’ PERCEPTION TOWARD MERDEKA CURRICULUM IMPLEMENTATION THROUGH PROJECT BASED LEARNING IN SPEAKING CLASS - Muh Shofiyuddin; Nina Sofiana; Santi Andriyani; Husni Mubarok (Universitas Islam Nahdlatul Ulama Jepara, 2023)
This study aims to find out how the students perception toward the implementation of Merdeka curriculum through Project based Learning in speaking class. It is a descriptive qualitative designn by using close questionnaire as the instrument of collecting data. the subjects of this study is semester four students having joined speaking for academic purposes consisting of 48 students. The result of analyzing the data shows that most of the students gave positive responses. The highest response, 100% of the students stated “yes” to the question if their speaking competence was increased by being taught using Project based Learning. Then, 80% students gave response “helpful” on the questioin, if Project based Learning help them improve your speaking skill. It can be concluded that the use implementation of Merdeka curriculum through Project based Learning gained very positive perception from the students.